ARTIFICIAL INTELLIGENCE IN EDUCATION: BENEFITS, CHALLENGES, AND IMPLICATIONS FOR MODERN TEACHING PRACTICES - Djurayeva Surayyo Vosiq qizi; Qurbonova Kamola O’ktam qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:Artificial Intelligence (AI) has emerged as one of the most influential technologies shaping contemporary education. The integration of AI-powered tools into  teaching  and  learning  environments  has  transformed  educational  practices  by enhancing  personalized  learning,  improving  assessment  processes,  and  increasing accessibility to educational resources. At the same time, the rapid expansion of AI technologies has raised significant concerns regarding academic integrity, data privacy, ethical considerations, and the potential reduction of human interaction in educational settings. This theoretical review examines the major advantages and disadvantages of AI in education through a comprehensive analysis of recent scholarly literature. The study explores how AI contributes to teaching effectiveness, student engagement, and learning  outcomes  while  also  addressing  challenges  associated  with  technological dependency and algorithmic bias. The findings indicate that AI has substantial potential to support educational innovation; however, its implementation should be guided by ethical  principles  and  pedagogical  objectives.  The paper  concludes  that  a  balanced integration of AI and human-centered teaching approaches is essential for maximizing educational benefits and minimizing associated risks.